The impact of exchange rate volatility on economic growth and international trade (Cultura Económica, 2022)
This paper summarizes several research works which deal with the different effects that the volatility of exchanges rates has on the economy. Among those effects, the most studied have been the effects on international trade and economic growth. Over the last five decades, there has been a debate at the theoretical level and different views at the empirical level on whether the gains from flexibility got under flexible exchange rates outweigh the losses from increased uncertainty which often prevails in such environment of flexible exchange rates. In particular, the impact of exchange rate volatility, both on international trade and economic growth, has been often discussed. This paper attempts to summarize some of the main results of these debates, concerning, in particular, the empirical evidence thus collected.